The influence of the textile substrate color on the contrast of thermochromic prints - Maričić Katarina; Kašiković Nemanja; Gvoka Teodora; Bošnjaković Gordana (Inovacijos Leidybos, Poligrafijos ir Multimedijos Technologijose)
Thermochromic inks have attracted much attention due to their application in various fields, including the textile industry. The application of these colors in sports clothing enables the monitoring of the athlete’s physiological state through the possibility of changing the color of the material under the influence of skin temperature. Due to the printing of thermochromic inks on textile materials used for visual control, there is a need to analyze the contrast of the printed elements. Contrast plays a significant role in visually highlighting shapes and details and also facilitates the recognition of printed parts and information on textile materials. Contrast analysis of thermochromic inks on different colors of textile materials plays a role in determining the optimal combination of base colors and thermochromic inks that will result in the most noticeable color change. This analysis allows designers and manufacturers to make good decisions about choosing the colors of textile materials when printing with thermochromic inks because, in this way, a high level of aesthetics and functionality is achieved. This work aims to compare and analyze the contrast of thermochromic inks on different colors of the substrate of different types of materials, as well as to determine whether the color of the fabric on which the thermochromic ink is printed affects the color contrast when it is changed, i.e., its discoloration and return to its original state. Magenta reversible thermochromic water-based leuco dye was used to print the samples. The work used textile materials for printing with different structures and different colors. The colors were chosen to be bright and to provide a good contrast with the magenta color so that their combination attracts the viewer’s attention and can create a strong visual effect. Colorimetric and contrast analyses determined that the color of the substrate is dependent on the contrast value. In the case of polyester textile material, the white color of the substrate showed the highest contrast values. On the other hand, in the case of printed samples on a material made of a mixture of polyester and elastane, it can be concluded that the gray color of the substrate gives the highest contrast values. In conclusion, the research highlights the importance of choosing colors and materials to achieve optimal results in the design and production of textile materials with thermochromic inks.